Defaultnomics: Making sense of the Barro-Ricardo equivalence in a financialized world - Lorenzo Esposito; Giuseppe Mastromatteo (Levy Economics Institute of Bard College, 2019)
The 2008 crisis created a need to rethink many aspects of economic theory, including the role of public intervention in the economy. On this issue, we explore the Barro-Ricardo equivalence, which has played a decisive role in molding the economic policies that fostered the crisis. We analyze the equivalence and its theoretical underpinnings, concluding that: (1) it declares, but then forgets, that it does not matter whether the nature of debt and investment is public or private; (2) its most problematic assumption is the representative agent hypothesis, which does not allow for an explanation of financialization and cannot assess dangers coming from high levels of financial leverage; (3) social wealth cannot be based on any micro-foundation and is linked to the role of the state as provider of financial stability; and (4) default is always the optimal policy for the government, and this remains true even when relaxing many equivalence assumptions. We go on to discuss possible solutions to high levels of public debt in the real world, inferring that no general conclusions are possible and every solution or mix of solutions must be tailored to each specific case. We conclude by connecting different solutions to the political balance of forces in the current era of financialization, using Italy (and, by extension, the eurozone) as a concrete example to better illustrate the discussion.
Keywords: E62; H23; F65; 330; Barro-Ricardo Equivalence; Financialization; Default